Book Review of Disciplinary Literacy and Gamified Learning in Elementary Classrooms: Questing Through Time and Space - Sheila Marie Noonen (Issues and Trends in Learning Technologies, 2023)
Disciplinary Literacy and Gamified Learning in Elementary Classrooms: Questing Through Time and Space is a handbook for launching quest-based learning activities in the elementary classroom. The work collates resources that support content area learning and multi-modal literacy. Students are centered in the learning activities as creators and players, thus making learning an active and engaging experience. Each unit articulates the learning standards, lesson objectives, and evaluation methods, effectively serving as a paradigm of best practices in teaching. This resource is complemented by an online resource hub for each unit of study, which includes a supplementary website, videos, and printable lesson plans.